SIMULASI MINIMUM SPANNING TREE GRAF BERBOBOT MENGGUNAKAN ALGORITMA PRIM DAN ALGORITMA KRUSKAL - Mohammad Yasin; Benny Afandi (FKIP Universitas Islam Jember, 2014)
There are so many problems that can be encountered by graphtechnique, especially in the realm of information technology (IT). One of the problems is to compute aMinimum Spanning Tree (MST). By using this kind of technique, it will be obtained a range of connected lines with its merits; e.g., the spanning tree of minimum cost, the least weight, and so on. There are commonly two algorithms to find minimum spanning tree (MST) namely Prim’s algorithm and Kruskal’s algorithm. This research aims to examine whether or not Prim’s algorithm and Kruskal’s algorithm can be used to calculate minimum spanning tree (MST) of a connected weighted graph, to know more about the approximate time to compute minimum spanning tree (MST) of a connected weighted graph through the implementation of Prim’s algorithm and Kruskal’s algorithm, and to find out which one of these two algorithms work best to calculate minimum spanning tree (MST) of a connected weighted graph. The development of software application in calculating MST using Prim’s algorithm and Kruskal’s algorithm is operated by Windows 7, the so-called Free Pascal Program, which includes the steps of observing and data gathering, the installation of the program, designing graph model that the weights are in accordance with the data gathered by Free Pascal Program, simulating the model of MST weighted graph through Prim’s algorithm and Kruskal’s algorithm by using Free Pascal Program to calculate the longest edge, the order of MST, computation time, and, lastly, to test and conclude the test result. The data simulation uses the data of PDAM pipeline “PerumnasPatrangJember”. The result shows that MST program used perfectly proved that Prim’s algorithm and Kruskal’s algorithm can be implemented to calculate the minimum spanning tree (MST) of a connected weighted graph. The MST program usedcan also simulate and calculate the length of the MST weighted graph through the implementation of Prim’s algorithm and Kruskal’s algorithm.Based on the test result, the run time of Kruskal’s algorithm is shorter and/or faster than the Prim’s algorithm to calculate a various MST weighted graph. Keywords: Simulation, Minimum Spanning Tree (MST), Prim’s algorithm, Kruskal’s algorithm, Free Pascal